Single-message-based cooperative authentication scheme for intelligent transportation systems. (December 2021) - Yang, Ming; Wei, Shuang; Jiang, Rongwang; Ali, Faizan; Yang, Boxiong
Highlights: Single-message cooperative authentication scheme for delay-computation cost balance. When a message arrives, a few vehicles are selected for message authentication. An authentication proof for faster cooperative authentication was constructed. Message evidence has high security and can counter a variety of malicious attacks. Abstract: Vehicle ad-hoc networks use message authentication to ensure message integrity and sender authenticity. However, this increases computational overhead. Collaborative message authentication uses message aggregation or batch verification to reduce the overall computational overhead, but this increases the authentication delay, resulting in a high message drop rate. In this paper, a single-message cooperative authentication scheme based on certificateless signatures is proposed, where a small number of vehicles verify the signature of a new message and construct the evidence, which can be used for rapid message verification and is difficult to forge. Security analysis shows that the message evidence has high security and can resist a variety of malicious attacks. The scheme implementation is simple, thus balancing the trade-off between authentication delay and total computational cost. Graphical abstract: Image, graphical abstract